The impact of Carbon Emissions Disclosure, Good Corporate Governance, and Media Disclosure on Investor Reaction - Ramadhani, Siti Fajriati; Cahya, Bayu Tri; Irawati, Tri; Hamdani, Lukman; cahyo, abdul latif dwi (LPPM Universitas Terbuka, 2024)
This research aims to determine the influence of Carbon emission Disclosure, Good Corporate Governance, and Media Exposure on investor reactions. The population used is energy companies listed on the Indonesian Sharia Stock Index for 2021-2022. The number of samples in the study was 70, using the purposive sampling method. Meanwhile, the research data used is secondary data in the form of annual reports obtained from the IDX and issuer websites. The analytical method used is multiple linear regression analysis. The research results show that disclosure of carbon emissions significantly negatively affects investor reactions. This is because there is still very little socialization from the company regarding operational activities in the environment towards the community as shareholders. Meanwhile, Good Corporate Governance and Media exposure significantly affect investor reactions.